Evaluación de alternativas de control no convencionales de ácaros del género tetranychus urticae en dos variedades de rosas. - Hidalgo Osorio, Anita Lucía (2021)
The species of mites Tetranychus urticae currently produces considerable qualitative and quantitative losses in the cultivation of roses under greenhouse, its control with conventional pesticides is massive and expensive, therefore it is necessary to evaluate by comparative analysis the efficiency parameters of the biological controllers of mites of the genus Tetranychus urticae. The field phase was carried out at the CONFLOR company located in the Pujilí canton, in two varieties of roses (mondial and véndela) in conventional greenhouse production, where six unconventional control alternatives were applied: predators, bacteria and entomopathogenic fungi and Biological acaricides, in 12 treatments and 4 repetitions with a DPD divided plot design with random blocks with 48 experimental units in which the variables were evaluated in determined samples: percentage of incidence, percentage of severity, percentage of efficiency and degree of infestation . Through analysis of variance and orthogonal comparisons of the treatments, the predator Ambliseius californicus was determined as the most efficient vs Bacillus thuringiensis, Beauveria Bassiana, Natural extract 18% garlic and 22% chili pepper and Azadirachta indica; and that the unconventional control alternatives had greater effect and efficacy in the world variety.